Regional winter climate of the southern central Andes: Assessing the performance of ERA‐Interim for climate studies. Issue 14 (18th July 2014) - Rusticucci, Matilde; Zazulie, Natalia; Raga, Graciela B.
Abstract In order to determine the feasibility of using reanalysis (ERA‐Interim) for climate studies over the southern central Andes in South America, we have compared the most recent version of different data sets available to the community. The data sets include gridded in situ observations: Climate Research Unit (CRU), Global Precipitation Climatology Centre (GPCC), and University of Delaware; merged satellite and in situ data: Global Precipitation Climatology Project; and satellite estimates: Tropical Rainfall Measuring Mission. We pay particular attention to the region between 30° and 37°S and also the period 1970–1976 to evaluate the data sets. This is the period of maximum availability of meteorological stations in the region. Whereas all data sets provide an adequate representation of mean winter, GPCC provides the best for winter precipitation due to the large number of stations included in gridding. The CRU data set has fewer observations throughout the period. Although it cannot reproduce the localized maxima in the Andes, it provides a better representation of the regional precipitation and is best suited to evaluate trends. The temperature in the region is best estimated by CRU. We evaluate the ERA‐Interim reanalysis to determine potential shortcomings. The trends in the region were analyzed during the period 1979–2010, and while CRU indicates a significant decrease in winter precipitation, ERA‐Interim shows virtually no significant trends. Interannual variability is well represented by ERA‐Interim, and the El Niño–Southern Oscillation, which has been proven to be the principal source of year to year precipitation variability in the region, is highly correlated there.